INTEGRASI PENDIDIKAN AGAMA ISLAM DAN BIOLOGI DALAM MEMBANGUN KESADARAN EKOLOGIS MAHASISWA UIN SUNAN KALIJAGA - Eni Hidayati; Runtut Prih Utami; Eva Latipah; Abdul Latif (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the increasing environmental crisis, which indicates a low level of ecological awareness, including among university students, as well as the suboptimal integration of Islamic Religious Education and biology in the learning process. In fact, these two fields have great potential to develop holistic ecological awareness through the integration of Islamic values and scientific concepts. This study aims to describe the forms of integration between Islamic Religious Education and biology and to examine the extent of its implementation in fostering ecological awareness among students at UIN Sunan Kalijaga. This research employs a qualitative approach using a field research method, with data collection techniques including interviews, observations, and documentation. The results show that integration has been carried out by linking biological concepts with Islamic values such as khalifah (stewardship), amanah (trust), and environmental balance, both in the learning process and in daily practices. Students demonstrate increased ecological awareness reflected in behaviors such as maintaining environmental cleanliness, reducing plastic use, and using resources more wisely. However, the implementation of this integration is still uneven, tends to depend on individual lecturers, and has not been systematically structured within the curriculum. Therefore, it is necessary to strengthen integrative, contextual, and practice-based learning designs to more effectively and sustainably enhance students’ ecological awareness.